The microbial production of polyphenol oxidase enzyme systems and their application in the treatment of phenolic wastewaters - Scherman, Patricia Ann (neé Goetch) (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1992)
Phenolic compounds are a group of organic chemicals present in the wastewaters of many synthetic industrial processes. Due to their extreme toxicity to man and animals, and deleterious impact on the environment, a range of techniques exist for the effective treatment and disposal of these pollutants. Biological degradation using microbial enzymes presents a valuable alternative to conventional wastewater treatment systems. This research was therefore initiated to investigate the polyphenol oxidase enzyme system and the feasibility of its application for effluent treatment and studies in organic solvents. The enzyme system is widely distributed in nature, with Agaricus bisporus (the common mushroom) being the best known producer. Biochemical investigations of the enzyme system were therefore carried out using this extract. A screening programme was initiated to identify microbial polyphenol oxidase producers which could be cultured in liquid media, thereby enabling the production of large quantities of enzyme in fermentation systems. Extensive growth optimization and enzyme induction and optimization studies were carried out on selected cultures. A number of good producers were isolated, namely a bacterial culture designated AECI culture no. 26, Streptomyces antibioticus, Streptomyces glaucescens and a manipulated strain, Streptomyces lividans (pIJ702). Enzyme production by Agaricus bisporus mycelia was optimized in deep-liquid culture; enzyme extracts showed high phenol removal efficiencies. Streptomyces antibioticus, Streptomyces glaucescens, Streptomyces lividans (pIJ702) and AECI culture no. 26 whole cells were also investigated for phenol-removing ability in simulated phenolic effluents. The use of whole cells reduces enzyme inactivation and instability due to the protection of the enzyme system within the cell. All cultures showed improved removal efficiencies in phenolic growth media. These results strongly suggest their use for phenol removal in continuous systems.
Keywords: Phenol oxidase; Water -- Purification -- Biological treatment; Enzymes -- Regulation